An Examination of the Usage of Vocabulary Retention Techniques (VRTs) of Thai Undergraduate EFL Students - Jenpattarakul, Win (Mediterranean Journal of Social Sciences, 2012)
This study aimed to 1) investigate the usage of vocabulary retention techniques (VRTs) of the second-year students atBangkok University 2) compare the usage of vocabulary retention techniques (VRTs) between achievers and underachievers 3)compare the usage of vocabulary retention techniques (VRTs) of the second-year students who have different reading behavioroutside of class. The instruments used for collecting data were a questionnaire and an in-depth interview. Proportional stratifiedrandom sampling was employed to formulate a sample of 364 students from nine faculties of Bangkok University. The data werestatistically analyzed in terms of mean and standard deviation. t-Test analysis was used to find the difference between achieversand underachievers on the usage of vocabulary retention techniques (VRTs). In addition, One-way Analysis of Variance(ANOVA) and Welch test were used to compare the usage of vocabulary retention techniques (VRTs) of students with differentreading behavior outside of class. For the in-depth interview, six underachievers and six achievers were randomized through asimple random sampling technique to give their opinions on the questions provided, and the data were collected to assure theresults of the study. The results of this study showed that the overall usage of vocabulary retention techniques (VRTs) ofBangkok University students was at a medium level, and significant differences existed in vocabulary retention techniques(VRTs) usage between the achievers and underachievers and of the students with different reading behavior outside of class.The findings of this research would help the teachers to improve the process and material for teaching and learning vocabularyretention techniques (VRTs) and raise awareness of vocabulary retention techniques(VRTs) among the students in order toenhance the students’ lexical competence which can develop their reading comprehension. Pedagogical implications intoteaching vocabulary retention techniques (VRTs) were suggested.